THE IMPACT OF HEALTH ON ECONOMIC DEVELOPMENT: AN INDIAN PERSPECTIVE (International Journal of Food and Nutritional Sciences, 2022)
I have discussed the topic in one of my artical on how the Impacts of Health on Economic Development. Here I have mainly discussed about the role of health in economic development and how it is broad and also the importance of health according to the World Health Organization has been explained. The present health in india explained. The nature of health in is indian’s Economic development has also been found and remedied. Health care of Economic development in india at present is also explained. Finally a Bibliography is provided in related to my article to complement it.